2017
DOI: 10.6065/apem.2017.22.3.158
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-to-high density lipoprotein cholesterol ratio in overweight Korean children and adolescents

Abstract: Purpose The triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio has recently been reported as a biomarker of cardiometabolic risk in obese children and adolescents. The purpose of this study is to describe the TG/HDL-C ratio and related factors in overweight and normal weight Korean children and to evaluate whether the high TG/HDL-C ratio is associated with insulin resistance in overweight children and adolescents.MethodsData from 255 overweight (aged 8.7±2.0 years) and 514 normal weight (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
2
17
1
1
Order By: Relevance
“…Both TG/HDL-C and non-HDL-C correlate well with the increased number of sd-LDL-C particles, however based on AUC, non-HDL-C appears to be slightly better when compared to the TG/HDL-C ratio in the diagnosis of dyslipidemias among children in non-fasting condition [ 15 ]. Yoo et al showed TG/HDL-C to be a good predictor of cardiovascular disease in obese children and adolescents, as well as highlighting on association with insulin resistance, though recent lipid screening guidelines for children recommend non-HDL-C as a universal screening test in non-fasting condition [ 25 ]. In agreement with the Bogalusa Heart Study and the National Heart, Lung, and Blood Institute, non-HDL-C is considered a reliable marker in the screening of dyslipidemias in children [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both TG/HDL-C and non-HDL-C correlate well with the increased number of sd-LDL-C particles, however based on AUC, non-HDL-C appears to be slightly better when compared to the TG/HDL-C ratio in the diagnosis of dyslipidemias among children in non-fasting condition [ 15 ]. Yoo et al showed TG/HDL-C to be a good predictor of cardiovascular disease in obese children and adolescents, as well as highlighting on association with insulin resistance, though recent lipid screening guidelines for children recommend non-HDL-C as a universal screening test in non-fasting condition [ 25 ]. In agreement with the Bogalusa Heart Study and the National Heart, Lung, and Blood Institute, non-HDL-C is considered a reliable marker in the screening of dyslipidemias in children [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their levels of total cholesterol (TC) were 172.0 mg/dL, low-density lipoprotein cholesterol (LDL) was 106.54 mg/dL and they had a high-density lipoprotein cholesterol (HDL) of 50.0 mg/dL (171.0, 101.0 and 49.0 mg/dL, as averages of the last three years, respectively). Concerning to triglycerides (TG), girls showed a concentration of 90.0 mg/dL in the latest year (86.0 mg/dL as median for three years), and thus the risk scores for atherosclerosis (TC/HDL ratio) and that for insulin resistance (TG/HDL ratio) were 3.46 and 1.67, respectively (3.57 and 1.84 for the last three years), which fell within the normal ranges [23][24][25]. Body mass index (BMI) was 21.25 kg/m 2 , with BMI-SDS of 0.59 and height-SDS of −0.77, and their waist circumference (WC) was 71.77 cm (Table 1).…”
Section: Characterization Of the Uncontrolled T1dm Populationmentioning
confidence: 89%
“…They exhibited TC levels of 163.5 mg/dL and had an LDL of 98.32 mg/dL and HDL of 43.5 mg/dL (169.5, 96.0 and 49.0 mg/dL as averages of the last three years, respectively). In boys, the median of TG levels was 83.5 mg/dL (80.0 mg/dL in the last three years) and thus the ratios for TC/HDL and TG/HDL were 3.44 and 1.71, respectively (3.39 and 1.72 in the last 3 years), falling also within the safety ranges [23][24][25]. The BMI was 20.61 kg/m 2 , with BMI-SDS of 0.51 and height-SDS of −0.80, and the WC was 71.06 cm (Table 1).…”
Section: Characterization Of the Uncontrolled T1dm Populationmentioning
confidence: 93%
“…Whole IR was calculated with HOMA-IR according to Matthews et al 26 , and children were classified as having IR according to cutoff values from previous work in Mexican population 27 . The TG/high-density lipoprotein cholesterol index (I-TG/HDL-C) was calculated, which is an indirect method for IR proposed by Quijada et al 28 , and values > 2.0 were considered as a cardiovascular risk factor 29 .…”
Section: Biochemical Measurementsmentioning
confidence: 99%